Determinants of Income Inequality in East Java Province: An Analysis of Demographic, Social, and Economic Factors - Diah Ayu Pratiwi; Farida Rahmawati (Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Income inequality is a structural development problem that can trigger social conflict, affect long-term economic growth, and hinder the achievement of SDGs. The purpose of this study is to analyze the factors that contribute to income inequality in East Java Province by combining demographic, social, and economic factors. The data used includes panel data from 38 districts and cities in East Java Province between 2017 and 2023 period. The analysis method used is panel data regression with a fixed effect model. To measure the effect of variables on income inequality, the testing was conducted partially and simultaneosly. The individual test results show that elderly dependency and poverty have a positive and significant relationship, while the human development index and economic growth are proportional but not significantly, and the open unemployment rate is not significant negative. Simultaneously, all variables have a significant effect on income inequality of 55.67 percent, with the remaining 44.37 percent influenced by variables outside the scope of this study.